Transcription factors in microcephaly - Lim, Youngshin (Frontiers in Neuroscience, 2023)
Higher cogniNon in humans, compared to other primates, is oWen aXributed to an increased brain size, especially forebrain corNcal surface area. Brain size is determined through highly orchestrated developmental processes including neural stem cell proliferaNon, neurogenesis, migraNon, laminaNon, arborizaNon, and apoptosis. DisrupNon in these processes oWen result in either a small (microcephaly) or large (megalencephaly) brain. One of the key mechanisms controlling these developmental processes is the spaNal and temporal transcripNonal regulaNon of criNcal genes. In humans, microcephaly is defined as a condiNon with a significantly smaller head circumference of an individual compared to the average head size of a given age and sex group. Growing number of genes are idenNfied as associated with microcephaly, and among them are the genes involved in transcripNonal regulaNon. In this review, a subset of genes encoding transcripNon factors (e.g., homeobox-, basic helix-loop-helix, forkhead box-, high mobility group box-, and zinc finger-domain containing transcripNon factors), whose funcNons are important for corNcal development and implicated in microcephaly, are discussed.